Znaczenie podejścia partycypacyjnego w promocji zdrowia i profilaktyce nowotworowej - Leksy, Karina (Studia Edukacyjne, 2020)
Leksy Karina, The Significance of the Participatory Approach in Health Promotion and Cancer Prevention [Znaczenie podejścia partycypacyjnego w promocji zdrowia i profilaktyce nowotworowej]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 309-321. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.17 The global spread of cancer makes every preventive action aiming at stopping the increase in number of cases and deaths related to cancer extremely important. Preventive actions may be especially effective in diseases etiologically related to lifestyles, including above all eating habits and level of physical activity. It is worth implementing them in compliance with the participatory approach, which constitutes a key component of health promotion and health education. The aim of this article is to present the reasons for and the need to implement prevention based on the idea of participation. This is justified by the results of the research conducted as part of a grant sponsored by Polska Liga Walki z Rakiem [Polish Cancer League] (“Onkogranty II” contest), entitled Promotion of healthy eating habits and physical activity in primary schools throughout the city of Bytom – a diagnosis of educational needs in the context of planning effective actions in primary cancer prevention. It seems that involving students in the process of identifying needs, determining priorities, planning and evaluating these actions is currently one of the most effective ways of developing awareness of cancer prevention.